Electrode assembly and lithium secondary battery
By forming a polymer or ceramic particle coating with a high absolute zeta potential on the separator of the lithium-ion secondary battery, the safety hazards caused by the shrinkage of the separator at high temperature are solved, and the high-temperature safety and conductivity of the battery are improved.
Patent Information
- Application Number
- JP2024562908
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-05
- Filing Date
- 2023-09-06
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-09-06
AI Technical Summary
Existing lithium-ion secondary batteries have safety risks in high-temperature environments, especially due to the short circuit and fire risks of positive and negative electrodes caused by the reduction of the separator at high temperature.
The coating layer with polymer or ceramic particles with an absolute zeta potential of 25 mV or more is used to enhance the viscosity strength between the separator and the coating so that its 90° peel strength at 60°C is between 30 gf/25mm and 140 gf/25mm.
Effectively prevent the separator from shrinking at high temperatures, avoiding the risk of short circuits of positive and negative electrodes and fire, while ensuring lithium ion conductivity and reducing the internal resistance of the battery.
Smart Images

Figure 2025514123000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0113106 dated September 6, 2022 and Korean Patent Application No. 10-2023-0117680 dated September 5, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to an electrode assembly and a lithium secondary battery. [Background technology]
[0003] With the development of technology and increasing demand for electric vehicles and energy storage systems (ESS), the demand for batteries as energy sources is rapidly increasing, and research on batteries that can meet various requirements is being conducted.In particular, active research is being conducted on lithium secondary batteries, which have high energy density and excellent life and cycle characteristics as a power source for such devices.
[0004] In general, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, etc. The positive electrode may generate oxygen due to an unstable structure in a charged state, and if oxygen is generated, there is a high risk of fire. Therefore, research and development of a method for improving the safety of lithium secondary batteries is being attempted.
[0005] The separator is used to ensure electrical insulation between the positive and negative electrodes, and a thin film made of polyolefin is generally used. However, polyolefin-based separators tend to shrink in high-temperature environments, and may fail to provide insulation between the positive and negative electrodes. If electrical insulation between the positive and negative electrodes is not possible, a short circuit may occur, which may cause fire due to the interaction with oxygen generated by an unstable positive electrode. That is, if a short circuit occurs in a lithium secondary battery in a charged state in a high-temperature environment, the lithium secondary battery may catch fire.
[0006] Therefore, there is a need for technological development to improve the high temperature safety of lithium secondary batteries. Summary of the Invention [Problem to be solved by the invention]
[0007] Therefore, the present invention provides an electrode assembly that improves the high-temperature stability of a lithium secondary battery while maintaining excellent electrochemical properties, and a lithium secondary battery including the electrode assembly. [Means for solving the problem]
[0008] According to one embodiment of the present invention, there is provided an electrode assembly including a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a coating layer formed on one surface of the separator and including polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more, wherein the 90° peel strength between the separator and the coating layer measured at 60°C is 30 gf / 25 mm to 140 gf / 25 mm.
[0009] In the electrode assembly, the coating layer can be in direct contact with the positive electrode.
[0010] In the electrode assembly, a ratio D1 / D2 of a thickness (D1) of the coating layer to a thickness (D2) of the separator may be 0.1-4.
[0011] In the electrode assembly, the coating layer may have a thickness (D1) of 30 μm or less.
[0012] In the electrode assembly, the separator may have a thickness (D2) of 5 μm to 20 μm.
[0013] In the electrode assembly, the polymer particles having an absolute value of a zeta potential of 25 mV or more may include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, and polyethylene terephthalate.
[0014] In addition, the ceramic particles may include one or more selected from the group consisting of boehmite (γ-AlO(OH)), Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, and MnO. In another example, the ceramic particles may be ceramic particles containing lithium and having ion conductivity, for example, lithium-containing oxide or lithium-containing phosphate particles. Specific examples thereof include one or more selected from the group consisting of LAGP (lithium aluminum germanium phosphate)-based compounds, LLZO (lithium lanthanum zirconium oxide)-based compounds, LATP (lithium aluminum titanium phosphate)-based compounds, LLZTO (lithium lanthanum zirconium tantalum oxide)-based compounds, LLTO (lithium lanthanum titanium oxide)-based compounds, LSTP (lithium silicon titanium phosphate)-based compounds, LGPO (lithium germanium phosphate)-based compounds, and lithium oxides (e.g., Li2O).
[0015] The polymer particles or ceramic particles have an average particle size (D 50 The coating layer may include a polymer binder and the polymer particles or ceramic particles dispersed on the polymer binder, and the weight ratio of the polymer binder to the polymer particles or ceramic particles may be 1:9 to 5:5.
[0016] According to another embodiment of the invention, there is provided a lithium secondary battery comprising the above-mentioned electrode assembly and a flame-retardant electrolyte comprising a flame-retardant solvent having a flash point of 100° C. or more or no flash point, and a lithium salt.
[0017] In this case, the flame-retardant solvent may include one or more organic solvents having a functional group selected from the group consisting of a sulfone-based functional group, a fluorine-containing functional group, a phosphorus-containing functional group, and a nitrile-based functional group, and more specifically, may include one or more organic solvents selected from a sulfone-based compound, a nitrile-based compound, a phosphorus-based compound, and a fluorine-substituted carbonate-based compound. Effect of the Invention
[0018] In the case of the electrode assembly according to the present invention, the 90° peel strength between the separator and the coating layer measured at 60°C is 30 to 140 gf / 25 mm. When the adhesive strength between the separator and the coating layer satisfies the above range, the separator attached to the coating layer does not easily shrink even in a high-temperature environment, thereby preventing a short circuit between the positive electrode and the negative electrode, and improving the high-temperature safety of the lithium secondary battery. In addition, when the adhesive strength between the separator and the coating layer satisfies the above range, it is possible to minimize the problem of an increase in cell resistance due to a decrease in the conductivity of lithium ions at the interface between the separator and the coating layer caused by the pores in the separator being excessively clogged by particles contained in the coating layer.
[0019] In addition, since the polymer particles and / or ceramic particles contained in the coating layer have a melting point relatively higher than that of polyolefin-based polymers, the coating layer containing the particles does not easily shrink at high temperatures. Therefore, the coating layer suppresses the thermal shrinkage of the separator, thereby preventing short circuits between the positive and negative electrodes at high temperatures and improving the high temperature safety of the lithium secondary battery.
[0020] Meanwhile, when a flame-retardant electrolyte is used to ensure the high temperature safety of a lithium secondary battery, the flame-retardant electrolyte has a problem of poor wetting of a polyolefin-based separator, resulting in reduced lithium ion mobility in the separator. However, when the coating layer formed on the separator of the present invention contains polymer particles and / or ceramic particles having an absolute value of a zeta potential of 25 mV or more, the coating layer can be easily impregnated with the flame-retardant electrolyte, thereby ensuring lithium ion mobility. [Brief description of the drawings]
[0021] [Figure 1] 2 is a graph showing voltage-temperature changes over time for the lithium secondary battery produced in Example 1. [Diagram 2] 4 is a graph showing the voltage-temperature change over time of the lithium secondary battery produced in Example 2. [Diagram 3] 1 is a graph showing the voltage-temperature change according to time for the lithium secondary battery produced in Example 3. [Figure 4] 1 is a graph showing the voltage-temperature change according to time for the lithium secondary battery produced in Example 4. [Diagram 5] 1 is a graph showing voltage-temperature changes over time for a lithium secondary battery produced in Comparative Example 1. [Figure 6] 1 is a graph showing voltage-temperature changes over time for a lithium secondary battery produced in Comparative Example 2. [Figure 7] 1 is a graph showing voltage-temperature changes over time for a lithium secondary battery produced in Comparative Example 3. [Figure 8] 1 is a graph showing voltage-temperature changes over time for a lithium secondary battery produced in Comparative Example 4. [Figure 9] 13 is a graph showing voltage-temperature changes according to time for the lithium secondary battery produced in Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The advantages and features of the present invention, and the method of achieving them, will become clear by referring to the following detailed examples in conjunction with the accompanying drawings. However, the present invention is not limited to the following disclosed examples, and can be realized in various different forms. The embodiments are provided to complete the disclosure of the present invention and fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is defined only by the scope of the claims. The same reference numerals refer to the same elements throughout the specification.
[0023] Unless otherwise defined, all terms (including technical and scientific terms) used herein will be used in the sense commonly understood by those having ordinary skill in the art to which the present invention belongs. Furthermore, terms defined in commonly used dictionaries will not be interpreted ideally or excessively unless clearly and specifically defined.
[0024] The terms used in the present specification are for the purpose of describing the embodiments and are not intended to limit the present invention. In the present specification, the singular form includes the plural form unless otherwise specified in the text. The words "comprises" and / or "comprising" used in the specification do not exclude the presence or addition of one or more other components other than the components mentioned.
[0025] In this specification, when a part includes a certain component, this does not mean to exclude other components, but means that it may further include other components, unless specifically stated to the contrary.
[0026] In this specification, the phrase "A and / or B" means A, or B, or A and B.
[0027] In this specification, "%" means % by weight unless otherwise specified.
[0028] In this specification, D 50means a particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 can be measured by using, for example, the laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.
[0029] In this specification, the 90° peel strength between the separator and the coating layer was measured by preparing a separator having a coating layer on one side thereof with a width of 25 mm, attaching the separator to a slide glass with double-sided tape, and rolling the separator twice with a 2 kg roller. The coating layer was then peeled from the separator at a distance of 90 mm from the separator at a speed of 300 mm / min under a temperature condition of 60°C, and the average 90° peel strength was measured.
[0030] In the present specification, "zeta potential" is an index showing the degree of surface charge of a particle. In the present invention, the zeta potential of a particle can be measured by electrophoretic light scattering using a dynamic light scattering device. Specifically, polymer particles or ceramic particles can be dispersed in water or an alcohol-based solvent without a dispersant, and then the zeta potential value of the particle can be measured by electrophoretic light scattering.
[0031] The present invention will now be described in further detail.
[0032] <Electrode Assembly> According to one embodiment of the present invention, the electrode assembly includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and a coating layer formed on one surface of the separator and including polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more, and the 90° peel strength between the separator and the coating layer measured at 60°C is 30 gf / 25 mm to 140 gf / 25 mm.
[0033] The coating layer may be formed on one side of the separator. In this case, the 90° peel strength between the separator and the coating layer measured at 60°C may be 30gf / 25mm to 140gf / 25mm, specifically 35gf / 25mm to 135gf / 25mm, more specifically 35gf / 25mm to 100gf / 25mm. If the 90° peel strength between the separator and the coating layer measured at 60°C is too small, the adhesive strength between the separator and the coating layer is weak, and the separator may thermally shrink at high temperatures, causing a short circuit between the positive and negative electrodes, which may lead to a risk of the battery catching fire. If the 90° peel strength between the separator and the coating layer measured at 60°C is too large, the pores in the separator may be excessively clogged by the particles contained in the coating layer, resulting in a problem of a decrease in the conductivity of lithium ions at the interface between the separator and the coating layer and an increase in cell resistance.
[0034] In the electrode assembly according to the embodiment, the coating layer may be in direct contact with the positive electrode. In this case, a separator is disposed between the coating layer and the negative electrode, so that the coating layer is not in direct contact with the negative electrode. This prevents the coating layer from coming into direct contact with the negative electrode, thereby preventing an irreversible reaction in which the polymer in the coating layer is reduced and decomposed during operation of the battery, and thus prevents a problem of a decrease in cycle life characteristics of the battery.
[0035] The ratio D1 / D2 of the thickness (D1) of the coating layer to the thickness (D2) of the separator may be 0.1 to 4, specifically 0.2 to 3, and more specifically 0.3 to 2. If D1 / D2 is less than 0.1, the coating layer is too thin compared to the separator, and sufficient adhesive strength between the separator and the coating layer is not ensured, which may cause the separator to heat shrink at high temperatures. If D1 / D2 is more than 4, the coating layer is too thick compared to the separator, and the lithium ion conductivity in the coating layer decreases, which may increase the cell resistance.
[0036] Meanwhile, in an electrode assembly, when only a coating layer is disposed between a positive electrode and a negative electrode without a separator, the coating layer must be formed thick to prevent a short circuit between the positive electrode and the negative electrode. However, when both a coating layer and a separator are used in the electrode assembly as in the above embodiment, the coating layer can be formed thin on the separator.
[0037] Specifically, the thickness (D1) of the coating layer may be 30 μm or less, preferably 1 μm to 20 μm, and more preferably 3 μm to 15 μm. When the thickness of the coating layer satisfies the above range, a short circuit between the positive electrode and the negative electrode is prevented, while sufficient adhesive strength between the separator and the coating layer is ensured to prevent the separator from shrinking at high temperatures.
[0038] In the electrode assembly according to the embodiment, the coating layer on the separator may include at least one of polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more.
[0039] At this time, the zeta potential of the polymer particles or ceramic particles is an index indicating the surface charge level of the particles, and can define the electrostatic repulsion or dispersibility of the particles. The polymer particles or ceramic particles having a large absolute value of the zeta potential can be uniformly dispersed on the separator, exhibiting good and uniform coating properties, and can define a large number of fine and uniform pores between the particles that allow lithium ions to pass through. In addition, the particles having such a zeta potential can cause the coating layer to exhibit excellent impregnation with a flame-retardant electrolyte containing a flame-retardant solvent. The combination of the coating layer and the flame-retardant electrolyte can cause a lithium secondary battery including the electrode assembly of the embodiment to exhibit excellent electrochemical properties.
[0040] The zeta potential of the polymer particles or ceramic particles can be measured by electrophoretic light scattering using a dynamic light scattering device. In this case, the zeta potential of the polymer particles or ceramic particles can be measured in a state where the polymer particles or ceramic particles are dispersed in water or an alcohol-based solvent without a separate dispersant. In a specific example, the zeta potential can be measured in a state where the polymer particles or ceramic particles are dispersed in an aqueous solvent at 0.1 wt % or less.
[0041] The absolute value of the zeta potential of the polymer particles or ceramic particles may be 25 mV or more, or 35 mV or more, or 45 mV or more, and may be 100 mV or less, or 90 mV or less, or 80 mV or less. Within such a range, good coating properties and porosity of the coating layer are achieved, high impregnation of the flame-retardant electrolyte is ensured, and a uniform reaction occurs throughout the electrode, thereby improving various performances of the lithium secondary battery, such as capacity, output, and life characteristics.
[0042] Specific examples of the polymer particles include one or more selected from the group consisting of polyethylene oxide (PEO), polymethyl(meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, polyethylene terephthalate, and polyphenylene sulfide.
[0043] Specific examples of the ceramic particles include one or more selected from the group consisting of boehmite (γ-AlO(OH)), Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, and MnO.
[0044] In another example, the ceramic particles may be ceramic particles containing lithium and having ion conductivity, for example, lithium-containing oxide or lithium-containing phosphate particles.Specific examples thereof include at least one selected from the group consisting of LAGP (lithium aluminum germanium phosphate)-based compounds, LLZO (lithium lanthanum zirconium oxide)-based compounds, LATP (lithium aluminum titanium phosphate)-based compounds, LLZTO (lithium lanthanum zirconium tantalum oxide)-based compounds, LLTO (lithium lanthanum titanium oxide)-based compounds, LSTP (lithium silicon titanium phosphate)-based compounds, LGPO (lithium germanium phosphate)-based compounds, and lithium oxides (e.g., Li2O).
[0045] The zeta potential of the polymer particles or ceramic particles can be adjusted not only by the type of each particle, but also by the particle size or surface properties of these particles. Therefore, in order to achieve the zeta potential, dispersibility, or appropriate porosity of the coating layer of the polymer particles or ceramic particles, the polymer particles or ceramic particles are adjusted to have an average particle size (D) of 300 nm to 3 μm, or 500 nm to 2.5 μm, or 700 nm to 2 μm. 50 ).
[0046] In order to control the surface properties of the polymer particles or ceramic particles and adjust the zeta potential, the polymer particles or ceramic particles are included in the coating layer after being surface-treated with plasma or ion beams.
[0047] Meanwhile, the coating layer may have a form including a polymer binder and the polymer particles or ceramic particles dispersed on the polymer binder. In this case, the same polymer as the binder contained in the electrode active material layer is used as the polymer binder, and specific examples thereof include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, nitrile rubber such as hydrogenated nitrile rubber, styrene-butadiene rubber, and fluororubber, and mixtures or copolymers of two or more selected from these may also be used. However, the specific composition of the polymer binder can be determined by those skilled in the art in consideration of the type and characteristics of the polymer particles or ceramic particles, and the method of forming the porous coating layer.
[0048] In addition, in consideration of the good coating properties and porosity of the porous coating layer and the good dispersibility of the particles, the coating layer may contain the polymer binder:polymer particles or ceramic particles in a weight ratio of 1:9 to 5:5, or 2:8 to 4:6.
[0049] The coating layer may have electrical insulation properties and may correspond to a porous insulating layer.
[0050] In addition, the coating layer does not easily shrink even at high temperatures, and therefore, when a separator having the coating layer is applied to an electrode assembly, a short circuit between the positive and negative electrodes can be prevented even in a high-temperature environment, thereby improving the high-temperature safety of the battery.
[0051] Meanwhile, the coating layer may be formed by coating a composition for forming a coating layer, which includes the polymer particles or ceramic particles and a polymer binder, on the separator, followed by drying and rolling.
[0052] In this case, the solid content of the composition for forming a coating layer may be 19% by weight to 25% by weight, specifically 19% by weight to 23% by weight, more specifically 19% by weight to 21% by weight. When the solid content of the composition for forming a coating layer satisfies the above numerical range, the composition for forming a coating layer may have a viscosity at a level that allows it to be coated on a separation membrane.
[0053] The viscosity of the composition for forming a coating layer at room temperature at 25° C. may be, for example, 1000 cP to 10000 cP, specifically 2000 cP to 7000 cP, more specifically 3000 cP to 5000 cP. When the viscosity of the composition for forming a coating layer satisfies the above numerical range, the composition for forming a coating layer is coated on the separation membrane with a uniform thickness.
[0054] Meanwhile, in order for the coating layer to have the above-mentioned peel strength range with respect to the separator, the coating layer can be formed by coating the composition for forming the coating layer on the separator, drying and rolling. In this case, the drying can be performed at a temperature of, for example, 60°C to 150°C for 0.5 hours to 12 hours. Furthermore, after such drying, the rolling can be performed at a pressure of, for example, 85 kg / cm. 2 ~160kg / cm 2 , or 90kg / cm 2 ~150kg / cm 2 The rolling can be performed 2 to 4 times, or 2 to 3 times, under the application of a pressure of 100 kg / cm 2 Super 160kg / cm 2 In the following cases, the rolling is preferably performed two or three times. By proceeding with the drying and rolling processes in this manner, the coating layer is formed on the separator with a predetermined peel strength, and a lithium secondary battery including the electrode assembly according to an embodiment may exhibit improved high temperature stability and excellent electrochemical properties.
[0055] On the other hand, the separator may be any one that is generally used as a separator in a lithium secondary battery without any particular limitation, and is preferably one that has low resistance to the ion transfer of the electrolyte and has excellent moisture-retaining ability for the electrolyte.
[0056] For example, the separation membrane may be a porous polymer film containing a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used as the separation membrane.
[0057] The thickness (D2) of the separator may be 5 μm to 20 μm, preferably 5 μm to 15 μm, and more preferably 6 μm to 13 μm. When the thickness of the separator is within the above range, the cell resistance value can be minimized while preventing a short circuit between the positive electrode and the negative electrode. As a result, the energy density of the lithium secondary battery can be prevented from decreasing, and the life characteristics can be improved.
[0058] Meanwhile, the positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.
[0059] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, the current collector may be stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.
[0060] The positive electrode current collector can have a thickness of 3 μm to 500 μm, and can have fine irregularities formed on the surface of the positive electrode current collector to enhance adhesion to the positive electrode active material layer. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0061] The positive electrode active material layer may contain a positive electrode active material, and may further contain a conductive material, a binder, and the like, as necessary.
[0062] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically, it can include compounds such as lithium metal oxides or lithium metal phosphates containing one or more metals such as iron, cobalt, manganese, nickel, or aluminum and lithium. More specifically, such compounds include lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), lithium-nickel-cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, p1 + q1 + r1 = 2), etc.), or lithium-nickel-cobalt-transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r2 M s2O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r2, and s2 are atomic fractions of independent elements, 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, and p2 + q2 + r2 + s2 = 1), etc.), lithium iron phosphate (e.g., Li 1+a Fe 1-x M x (PO 4-b )X b (where M is one or more selected from Al, Mg, and Ti, X is one or more selected from F, S, and N, -0.5 ≦ a ≦ 0.5, 0 ≦ x ≦ 0.5, 0 ≦ b ≦ 0.1), etc., and one or more of these compounds can be included.
[0063] Among them, in terms of being able to enhance the capacity characteristics and safety of the battery, the lithium metal oxide is LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), or lithium nickel manganese cobalt aluminum oxide (e.g., Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O2), lithium iron phosphate (e.g., LiFePO4), etc., and one or more mixtures of these can be used.
[0064] The positive electrode active material is contained in an amount of 60% to 99% by weight, preferably 70% to 99% by weight, and more preferably 80% to 98% by weight, based on the total weight of the positive electrode active material layer.
[0065] The positive electrode conductive material is a component for further improving the conductivity of the positive electrode active material. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery. For example, carbon powder such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers such as carbon fiber and metal fiber; carbon fluoride powder; conductive powder such as aluminum powder or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives can be used.
[0066] The positive electrode conductive material is usually contained in an amount of 1 to 20% by weight, preferably 1 to 15% by weight, and more preferably 1 to 10% by weight, based on the total weight of the positive electrode active material layer.
[0067] The positive electrode binder is a component that aids in binding the active material and conductive material and in binding them to the current collector.
[0068] Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene (PE), polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, various copolymers, and the like.
[0069] The positive electrode binder is usually contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of the positive electrode active material layer.
[0070] Meanwhile, the negative electrode may include a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. Alternatively, the negative electrode may be a graphite electrode made of carbon (C). Alternatively, the negative electrode may include lithium metal or be a metal current collector itself.
[0071] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like, an aluminum-cadmium alloy, or the like can be used.
[0072] The negative electrode current collector can usually have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the negative electrode current collector surface can be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0073] The negative electrode active material layer may contain a negative electrode active material, and may further contain a conductive material, a binder, and the like, as necessary.
[0074] The negative electrode active material may include at least one selected from the group consisting of lithium metal, a carbon material capable of reversibly intercalating / deintercalating lithium ions, a metal or an alloy of these metals and lithium, a metal composite oxide, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0075] As the carbon material capable of reversibly intercalating / deintercalating the lithium ions, any carbon-based negative electrode active material generally used in lithium ion secondary batteries can be used without particular limitation, and typical examples thereof include crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flaky, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, and the like.
[0076] As the metal or an alloy of these metals and lithium, a metal selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn, or an alloy of these metals and lithium is used.
[0077] Examples of the metal composite oxide include PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3 (0 ≦ x ≦ 1), Li x WO2 (0 ≦ x ≦ 1) and Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) can be selected and used from the group consisting of.
[0078] As the substance capable of doping and undoping lithium, Si, SiO x(0 < x ≤ 2), Si-Y alloy (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, Sn-Y (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), etc. may be mentioned, and at least one of these may be mixed with SiO2 and used. As the element Y, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof can be selected.
[0079] Examples of the transition metal oxide include lithium-containing titanium composite oxide (LTO), vanadium oxide, lithium vanadate, etc.
[0080] The negative electrode active material is contained in an amount of 60% by weight to 99% by weight, preferably 70% by weight to 99% by weight, more preferably 80% by weight to 98% by weight, based on the total weight of the negative electrode active material layer.
[0081] The negative electrode conductive material is a component for further improving the conductivity of the negative electrode active material, and such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and examples of the conductive material that can be used include carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystal structures; conductive fibers such as carbon fibers and metal fibers; carbon fluoride powder; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0082] The negative electrode conductive material is contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of the negative electrode active material layer.
[0083] The negative electrode binder is a component that helps to bond between the negative electrode conductive material, the negative electrode active material, and the negative electrode current collector. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, and various copolymers thereof.
[0084] The negative electrode binder is usually contained in an amount of 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, and more preferably 1 wt % to 10 wt %, based on the total weight of the negative electrode active material layer.
[0085] When a metal is used without forming a negative electrode active material layer in the negative electrode, the negative electrode may be manufactured by physically bonding, rolling, or depositing a metal thin film or a metal on the negative electrode current collector. The deposition method may be an electrochemical deposition method or a chemical vapor deposition method.
[0086] For example, the metal thin film itself or the metal bonded / rolled / deposited on the negative electrode current collector may include one metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In), or an alloy of two metals.
[0087] <Lithium secondary battery> Next, a lithium secondary battery according to another embodiment of the present invention will be described.
[0088] Such a lithium secondary battery may include the electrode assembly and the flame-retardant electrolyte described above, where the electrode assembly is as previously described.
[0089] The flame-retardant electrolyte may be an electrolyte that does not volatilize well and does not catch fire. Specifically, the flame-retardant electrolyte may be defined as an electrolyte containing a flame-retardant solvent and a lithium salt that has a flash point of 100°C or more or does not have a flash point. In this case, the flame-retardant solvent may include a substantially insoluble organic solvent that does not have a flash point and an organic solvent that has a high flash point of 100°C or more, or 100°C to 250°C, or 110°C to 200°C, and low volatility. The lithium secondary battery of another embodiment including the flame-retardant electrolyte containing such a flame-retardant solvent and a lithium salt may exhibit excellent high-temperature safety. The flash point that defines the flame-retardant solvent may be measured by a closed or open method according to the standard method of ASTM D3278.
[0090] Meanwhile, the flame-retardant electrolyte has a problem that it has low wetting ability with respect to separators for lithium secondary batteries (e.g., polyolefin-based separators), resulting in reduced lithium ion mobility in the separator. However, when the coating layer formed on the separator contains polymer particles and / or ceramic particles with an absolute value of a zeta potential of 25 mV or more, the coating layer can be easily impregnated with the flame-retardant electrolyte, thereby ensuring lithium ion mobility. Therefore, the electrochemical properties of the lithium secondary battery can be excellent.
[0091] The flame-retardant electrolyte may include a flame-retardant solvent and a lithium salt, in which case the flame-retardant solvent may act as a medium through which ions involved in the electrochemical reaction of the battery can move.
[0092] In a specific example, the flame-retardant solvent may be an organic solvent having a functional group that contributes to low volatility and flame retardancy or non-flammability, for example, a functional group selected from the group consisting of a sulfone-based functional group, a fluorine-containing functional group such as a fluorine-substituted hydrocarbon group, a phosphorus-containing functional group such as a phosphate group or a phosphonate group, and a nitrile-based functional group, and one or more of such organic solvents may be mixed and used. More specifically, the flame-retardant solvent may include one or more organic solvents selected from the group consisting of a sulfone-based compound, a nitrile-based compound, a phosphoric acid-based compound, and a fluorine-substituted carbonate-based compound.
[0093] Among these, the sulfone-based compound may be a cyclic sulfone-based compound or a linear sulfone-based compound, and specifically may include one or more selected from the group consisting of sulfolane, tetramethylene sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl-i-propyl sulfone, ethyl-i-butyl sulfone, i-propyl-i-butyl sulfone, i-propyl-s-butyl sulfone, and butyl-i-butyl sulfone.
[0094] The nitrile compound may include at least one selected from the group consisting of acetonitrile, succinotrile, adiponitrile, malonitrile, glutaronitrile, suberonitrile, and sebaconitrile.
[0095] In addition, the phosphoric acid compound may include at least one selected from the group consisting of dimethyl methyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl ethyl phosphate, dimethyl (2-methoxyethoxy) methyl phosphonate, diethyl (2-methoxyethoxy) methyl phosphonate, and triphenyl phosphate.
[0096] Further, the fluorine-substituted carbonate compound is bis(2,2,3,3-tetrafluoropropyl)carbonate, methyl-2,2,2-trifluoroethyl carbonate, ethyl-2,2,2-trifluoroethyl carbonate, propyl-2,2,2-trifluoroethyl carbonate, methyl-2,2,2,2',2',2'-hexafluoro-i-propyl carbonate, ethyl-2,2,2,2',2',2'-hexafluoro-i -propyl carbonate, di-2,2,2-trifluoroethyl carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoro-i-propyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolan-2-one, and bis(2,2,3,3-pentafluoropropyl) carbonate.
[0097] Meanwhile, the lithium salt is used as a medium for transferring ions in a lithium secondary battery. The lithium salt has, for example, Li as a cation. + The anion is F. - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 -, ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO2 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - and SCN - The composition may include at least one selected from the group consisting of:
[0098] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10, LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2) and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2), and preferably contains LiN(SO2CF3)2 in terms of excellent stability. In addition to these, lithium salts commonly used in electrolytes for lithium secondary batteries can be used without any restrictions.
[0099] The concentration of the lithium salt can be appropriately changed within a range that is normally usable, but in order to obtain an optimal effect of forming a coating for preventing corrosion on the electrode surface, it is contained in the electrolyte at a concentration of 1 M to 3 M, preferably a concentration of 1 M to 2.5 M, and more preferably a concentration of 1 M to 2 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics during high-temperature storage of the lithium secondary battery is sufficient, the viscosity of the flame-retardant electrolyte is appropriate, and the impregnation of the flame-retardant electrolyte is improved.
[0100] The lithium secondary battery may be manufactured by inserting the electrode assembly into a cylindrical or prismatic battery case and then injecting a flame-retardant electrolyte, or by impregnating the electrode assembly with a flame-retardant electrolyte and then inserting the resulting product into a battery case and sealing it.
[0101] The battery case may be one commonly used in the art, and may have any shape depending on the intended use of the battery, such as, but not limited to, a cylindrical shape, a square shape, a pouch shape, or a coin shape.
[0102] The lithium secondary battery according to another embodiment of the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a number of battery cells. Preferred examples of the medium- to large-sized device include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems (ESS).
[0103] The present invention will be described in more detail with reference to the following specific examples. However, the following examples are merely illustrative for the purpose of aiding in the understanding of the present invention and are not intended to limit the scope of the present invention. It is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical concept of the present description, and it is to be understood that such changes and modifications are within the scope of the appended claims.
[0104] Examples and Comparative Examples First, in the following examples, the zeta potential of the polymer particles or ceramic particles was measured by electrophoretic light scattering using a dynamic light scattering device (product name: ELS-Z) in a state where the polymer particles or ceramic particles were dispersed in a water solvent at a temperature of 25°C at a concentration of 0.1 wt% or less.
[0105] In addition, the flash point of the (flame-retardant) organic solvent contained in the (flame-retardant) electrolyte was measured by a closed-cup method according to the standard method of ASTM D93. Specifically, a sample container was filled with an organic solvent sample, the container was covered and sealed, and the sample container was heated at a constant rate according to the standard method. During heating, the sample container was periodically opened to check whether a flame was generated, and the temperature at the time when the flame was generated was measured as the flash point.
[0106] Example 1 Manufacturing of separation membrane-coating layer composite A polyolefin separation membrane (thickness: 10 μm) was prepared.
[0107] It has a zeta potential of -50 mV and an average particle size of D 50 A composition for forming a coating layer (solid content: 21 wt%, viscosity: 4000 cP) was prepared by dispersing 1 μm-sized polymethyl methacrylate (PMMA) polymer particles, hydrogenated nitrile rubber (H-NBR), and polyvinylidene fluoride (PVDF) in a weight ratio of 7:1:2 in N-methyl-2-pyrrolidone (NMP) solvent.
[0108] The composition for forming the coating layer is coated on a separator (thickness: 10 μm) made of polyolefin material, dried at 80° C. for 1 hour, and then subjected to a pressure of 100 kg / cm 2 The separator was rolled twice at a pressure of 100 .mu.m to prepare a separator-coating layer composite having a coating layer of 10 .mu.m thickness formed on one side of the separator.
[0109] (2) Manufacturing of electrode assemblies A 20 μm-thick copper (Cu) metal thin film was prepared as a negative electrode current collector, and a 75 μm-thick negative electrode was manufactured by forming a negative electrode active material layer containing artificial graphite as a negative electrode active material on one surface of the copper metal thin film.
[0110] A 15 μm-thick aluminum (Al) metal thin film was prepared as a positive electrode current collector, and Li(Ni 0.8 Mn 0.1 Co 0.1 A positive electrode having a thickness of 60 μm was produced by forming a positive electrode active material layer containing O2.
[0111] The coating layer formed on one side of the separator was brought into contact with the positive electrode, and the other side of the separator was brought into contact with the negative electrode to prepare an electrode assembly.
[0112] (3) Manufacture of lithium secondary batteries A flame-retardant electrolyte was prepared by dissolving LiN(SO2CF3)2(LiFSI) in a flame-retardant solvent sulfolane (flash point: about 165°C) to a concentration of 1.5 M. The electrode assembly was placed in a battery case, and the flame-retardant electrolyte was injected to prepare a lithium secondary battery.
[0113] Example 2 The coating layer-forming composition is coated on a separator, dried at 80° C. for 1 hour, and then subjected to a pressure of 100 kg / cm 2 A separator-coating layer composite was prepared in the same manner as in Example 1, except that a coating layer having a thickness of 8 μm was formed on one side of the separator by rolling four times at a pressure of 1000 μm.
[0114] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating layer composite prepared by the above method was used.
[0115] Example 3 The coating layer-forming composition is coated on the separator, dried at 80° C. for 1 hour, and subjected to a pressure of 90 kg / cm 2 A separator-coating layer composite was prepared in the same manner as in Example 1, except that a coating layer having a thickness of 11 μm was formed on one side of the separator by rolling twice at a pressure of 1.0 μm.
[0116] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating layer composite prepared by the above method was used.
[0117] Example 4 The coating layer-forming composition is coated on a separator, dried at 80° C. for 1 hour, and subjected to a pressure of 150 kg / cm 2 A separator-coating layer composite was prepared in the same manner as in Example 1, except that a coating layer having a thickness of 7 μm was formed on one side of the separator by rolling twice at a pressure of 1000 MPa.
[0118] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating layer composite prepared by the above method was used.
[0119] Comparative Example 1 A polyolefin separation membrane (thickness: 10 μm) was prepared.
[0120] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that a separator having no coating layer on one side was disposed between the positive electrode and the negative electrode.
[0121] Comparative Example 2 The coating layer-forming composition is coated on a separator, dried at 80° C. for 1 hour, and subjected to a pressure of 60 kg / cm 2 A separator-coating layer composite was prepared in the same manner as in Example 1, except that a coating layer having a thickness of 12 μm was formed on one side of the separator by rolling twice at a pressure of 1.0 μm.
[0122] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating layer composite prepared by the above method was used.
[0123] Comparative Example 3 The coating layer-forming composition is coated on a separator, dried at 80° C. for 1 hour, and then subjected to a pressure of 200 kg / cm 2 A separator-coating layer composite was prepared in the same manner as in Example 1, except that a coating layer having a thickness of 6 μm was formed on one side of the separator by rolling twice at a pressure of 1000 MPa.
[0124] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating layer composite prepared by the above method was used.
[0125] Comparative Example 4 The coating layer-forming composition is coated on the separator, dried at 80° C. for 1 hour, and subjected to a pressure of 80 kg / cm 2 A separator-coating layer composite was prepared in the same manner as in Example 1, except that a coating layer having a thickness of 11.5 μm was formed on one side of the separator by rolling twice at a pressure of 1.0 μm.
[0126] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating layer composite prepared by the above method was used.
[0127] Comparative Example 5 The coating layer-forming composition is coated on a separator, dried at 80° C. for 1 hour, and subjected to a pressure of 150 kg / cm 2 A separator-coating layer composite was prepared in the same manner as in Example 1, except that a coating layer having a thickness of 6.5 μm was formed on one side of the separator by rolling four times at a pressure of 1.0 μm.
[0128] An electrode assembly and a lithium secondary battery were manufactured in the same manner as in Example 1, except that the separator-coating layer composite prepared by the above method was used.
[0129] Experimental Example 1 - Evaluation of peel strength between separator and coating layer For the separator-coating layer composites prepared in Examples 1 to 4 and Comparative Examples 1 to 5, the 90° peel strength between the separator and the coating layer was measured.
[0130] Specifically, the separation membrane-coating layer composites produced in Examples 1 to 4 and Comparative Examples 1 to 5 were cut to a width of 25 mm, attached to a slide glass with double-sided tape, and then rolled twice with a 2 kg roller. The average 90° peel strength was measured while peeling the coating layer from the separation membrane at a distance of 90 mm from the separation membrane at a temperature of 60°C and a speed of 300 mm / min. The measurement results are shown in Table 1 below.
[0131] [Table 1]
[0132] Experimental example 2: High temperature safety evaluation of lithium secondary batteries The results of hot box tests performed on the lithium secondary batteries produced in Examples 1 to 4 and Comparative Examples 1 to 5 are shown in Figures 1 to 9. Specifically, the hot box tests were performed by increasing the temperature from 25°C at a rate of 10°C / min, holding the temperatures at 100°C, 120°C, 140°C, 150°C, 160°C, 170°C, and 180°C for 30 minutes each, and then increasing the temperature to 200°C at a rate of 2°C / min.
[0133] 1 to 4 are graphs showing the voltage-temperature changes over time for the lithium secondary batteries produced in Examples 1 to 4, and FIGS. 5 to 9 are graphs showing the voltage-temperature changes over time for the lithium secondary batteries produced in Comparative Examples 1 to 5.
[0134] Moreover, the temperatures at which the lithium secondary batteries of Examples 1 to 4 and Comparative Examples 1 to 5 ignite in the hot box test are shown in Table 2 below.
[0135] [Table 2]
[0136] As shown in FIGS. 1 to 9 and Table 2, in the case of Examples 1 to 4 in which the 90° peel strength between the separator and the coating layer is in the range of 30 gf / 25 mm to 140 gf / 25 mm, the separator does not thermally shrink even at high temperatures due to the strong adhesive strength between the separator and the coating layer, so the battery does not ignite and has excellent high temperature safety.
[0137] Meanwhile, in Comparative Example 1, in which no coating layer was formed on the separator, and in Comparative Examples 2 and 4, in which the 90° peel strength between the separator and the coating layer was lower than 30 gf / 25 mm, it was confirmed that the separator thermally contracted at high temperatures, causing a short circuit between the positive and negative electrodes, and the battery ignited at temperatures above 170°C.
[0138] Experimental Example 3: Evaluation of cell resistance of lithium secondary battery The cell resistance value was measured for each of the lithium secondary batteries produced in Examples 1 to 4 and Comparative Examples 1 to 5, and the results are shown in Table 3 below.
[0139] Specifically, the lithium secondary battery was charged to SOC50% at a constant current of 0.1C at 25°C, and then discharged for 10 seconds at a constant current of 1.5C. The 0.1 second resistance value and the resistance value from 0.1 seconds to 10 seconds were calculated from the voltage drop value that occurred at this time.
[0140] [Table 3]
[0141] As shown in Table 3, in Examples 1 to 4 in which the 90° peel strength between the separator and the coating layer is in the range of 30 gf / 25 mm to 140 gf / 25 mm, the cell resistance increases compared to Comparative Example 1 in which no coating layer was formed on the separator, but it can be seen that the difference is not large.
[0142] On the other hand, in Comparative Examples 3 and 5, in which the 90° peel strength between the separator and the coating layer is greater than 140 gf / 25 mm, it can be seen that the cell resistance is high because the lithium ion conductivity at the interface between the separator and the coating layer is low compared to Examples 1 to 4.
Claims
1. Positive electrode; Negative electrode; A separator disposed between the positive electrode and the negative electrode; and a coating layer formed on one surface of the separation membrane, the coating layer including polymer particles or ceramic particles having an absolute value of a zeta potential of 25 mV or more; The electrode assembly, wherein a 90° peel strength between the separator and the coating layer is 30 gf / 25 mm to 140 gf / 25 mm.
2. The electrode assembly of claim 1 , wherein the coating layer is in direct contact with the positive electrode.
3. Separation membrane thickness (D 2 ) versus coating layer thickness (D 1 ) ratio D 1 / D 2 2. The electrode assembly of claim 1, wherein:
4. The thickness of the coating layer (D 1 2. The electrode assembly of claim 1, wherein the thickness of the first electrode layer is 30 μm or less.
5. The thickness of the separation membrane (D 2 2. The electrode assembly of claim 1, wherein the thickness of the first electrode is 5 μm to 20 μm.
6. 2. The electrode assembly according to claim 1, wherein the polymer particles include at least one selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl (meth)acrylate, polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate, and polyethylene terephthalate.
7. The ceramic particles are boehmite (γ-AlO(OH)), Al 2 O 3 , TiO 2 , Fe 2 O 3 , SiO 2 , ZrO 2 , Co 3 O 4 , SnO 2 , NiO, ZnO, V 2 O 5 10. The electrode assembly of claim 1, comprising at least one selected from the group consisting of MnO, LAGP (lithium aluminum germanium phosphate) based compounds, LLZO (lithium lanthanum zirconium oxide) based compounds, LATP (lithium aluminum titanium phosphate) based compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) based compounds, LLTO (lithium lanthanum titanium oxide) based compounds, LSTP (lithium silicon titanium phosphate) based compounds, LGPO (lithium germanium phosphate) based compounds and lithium oxides.
8. The polymer particles or ceramic particles have an average particle size (D 50 10. The electrode assembly of claim 1, further comprising:
9. The electrode assembly of claim 1 , wherein the coating layer comprises a polymeric binder and the polymeric or ceramic particles dispersed on the polymeric binder.
10. The electrode assembly of claim 9, wherein the coating layer comprises the polymer binder:the polymer particles or ceramic particles in a weight ratio of 1:9 to 5:
5.
11. An electrode assembly according to any one of claims 1 to 10; and A lithium secondary battery comprising a flame-retardant electrolyte containing a lithium salt and a flame-retardant solvent having a flash point of 100° C. or more or having no flash point.
12. The lithium secondary battery according to claim 11, wherein the flame-retardant solvent comprises one or more organic solvents having a functional group selected from the group consisting of a sulfone-based functional group, a fluorine-containing functional group, a phosphorus-containing functional group, and a nitrile-based functional group.
13. 12. The lithium secondary battery according to claim 11, wherein the flame-retardant solvent comprises at least one organic solvent selected from the group consisting of sulfone-based compounds, nitrile-based compounds, phosphoric acid-based compounds, and fluorine-substituted carbonate-based compounds.
Citation Information
Patent Citations
Separator for lithium secondary battery and lithium secondary battery including same
CN116325331A
Separator for non-aqueous electrolytic solution secondary battery
JP2004227972A
Slurry for secondary battery porous films, manufacturing method thereof, porous film for secondary batteries, and secondary battery
JP2015162312A
Separation membrane, lithium battery employing separation membrane, and manufacturing method of separation membrane
JP2019133934A
Dispersant composition for secondary battery slurry and utilization thereof
JP2020140957A